Non-modifiable and modifiable factors affecting anxiety and depressive symptoms in young athletes - Mesquita Vieira, Matheus [UNESP]; Melo Neves, Lucas; Felisberto da Silva, Pedro Victor [UNESP]; Fernandes, Romulo Araújo [UNESP]; Leite da Silva Xavier, Rosana [UNESP]; Almeida Queiroz Rossi, Priscila [UNESP]; Juday, Valeria; Deslandes, Andrea; Lastella, Michele; Rossi, Fabricio E. [UNESP] (Taylor & Francis, 2025)
Objectives: The aim of the present study was to verify the association between non-modifiable (age categories, sex and race/ethnicity) and modifiable (sport modality, socioeconomic, training load, sleep, and eating disorder) factors with anxiety and depressive symptoms in young athletes. Methods: The sample was composed of 168 athletes engaged in national competitions from individual sports [swimming (n = 26) and badminton (n = 53)] and team sports [soccer (n = 28) and handball (n = 61)]. The coaches monitored the training load throughout the training week, and athletes completed self-reported questionnaires to assess sociodemographic data, sleep quality, eating disorders, and symptoms of anxiety and depression on the recovery day after a full week of pre-season training. Results: The prevalence of anxiety and depressive symptoms in young athletes were 14.3% and 25.6%, respectively, and female athletes presented higher rates of anxiety symptoms than males (30.8% vs. 11.3%; p = 0.015). Athletes from individual sports and athletes with 18 years or older showed higher depressive symptoms than younger (32.3% vs. 17.3%; p = 0.021). Athletes from the minority group showed higher depressive symptoms compared to the dominant group (41.9% vs. 20%; p = 0.005). The quality of sleep also influenced both anxiety (β = 5.430 [95%CI: 1.896 to 15.553]) and depressive symptoms (β = 5.292 [95%CI: 2.211 to 12.664)] in young athletes. Conclusion: In short, non-modifiable factors, such as sex and age categories, should be considered when anxiety and depressive symptoms are examined in young athletes. Modifiable factors such as sports modality and sleep quality impact depressive symptoms in this population.
Keywords: athletes; depression; Mental health; performance; sport